MODEL PEMBELAJARAN SPADE: SOLUSI KESULITAN BELAJAR MATEMATIKA PADA MATERI GEOMETRI DI SEKOLAH DASAR (TINJAUAN SISTEMATIS) - pajar reza; Epon Nur'aeni L; Muhammad Rijal Wahid Muharram (De Fermat : Jurnal Pendidikan Matematika, 2021)
The results of the Programme for international Students Assessment (PISA) in 2018 in the mathematics ability category of Indonesia ranked 73rd out of a total of 79 PISA participating countries. This arises because of the many learning obstacles or math learning problems faced by students. The purpose of this study was to decrypt spade learning model as a solution of the difficulty of learning geometry material in elementary school subjects. Spade learning model is a learning model based on traditional games. This study uses systematic review method by retrieving data on Google Scholar data base downloaded from June 20, 2021 to July 3, 2021. Obtained 57 appropriate articles, after selection that corresponds to the category of inclusion, the remaining 19 which then become research data to be studied. The end result of this study is that SPADE learning model is considered to be able to be a solution to math problems in elementary schools.